The Effect Of White Sugar Cristal Concentration Towards Red Peanut Selai Organoleptic Quality (Arachis hypogea) - Masuku, Mustamina Anwar (Agrikan: Jurnal Agribisnis Perikanan, 2018)
Jam is part of one of the food ingredients that tastes very sweet and can be made from various types of fruits, such as banana, pineapple, apple, strawberry, blueberry, apricot and grape jams. The sweet taste is due to the addition of white crystalline sugar in the product which shows its characteristic as jam. Various opinions of experts have stated that jam can be made from various kinds of fruit but no one has mentioned tubers or legumes or secondary crops. One of the most possible palawija plants is peanuts which have the potential to be used as ingredients for jam production. The purpose of this study was to determine the effect of variations in sugar concentration on the quality of peanut butter, especially on organoleptic parameters and is expected to provide new information about differences in sugar concentrations in peanut butter. This study used an experimental method, Completely Randomized Design (CRD) consisting of one factor with 5 (five) treatments and 3 (three) replications, so that there were 15 treatment units. Parameters observed include analysis of organoleptic properties of jam products such as color, taste, aroma and texture.